Socio-economic Status and Fishing Practices among Boat Owners in Batticaloa District, Sri Lanka - Croos, Rukshan Calistus; Mahidha, Naveenkumar; Murugavel, Deepak; Muthuvel, Arumugam; Shankar, Kanchana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Residents of the Batticaloa region of Sri Lanka depend on marine fishing, a major livelihood source for individuals in villages and towns. A comprehensive survey was conducted to determine local boat owner's socioeconomic status and fishing operations. A detailed questionnaire was prepared and data were collected from 74 boat owners. The collected data was about the socio-economic status, fishing period, crafts, and gears to analyze the fishing operations of the study area. The collected data was used to determine demographic characteristics like age, marital status, and literacy. Also helps to evaluate the living standards, and access the basic amenities including that are employment, basic utilities, and appliances. To these data, the socio-economic impacts of fluctuating income among the fishing communities are evaluated. The present result described that 30% of the respondents were in the age group of 50 to 59 years and 95% of respondents were married. The literacy rate of the respondents was 95.9% for fishing boat owners. The fishing boat owners have houses with basic utilities and appliances. Electricity and water sources are available in 100% of respondents' houses. 97% of the respondent's houses have landline or mobile and motorized transport. 76.58% of respondents had difficulties getting the appliances to prepare food. Additionally, FAO policies and programs that in practice to promote & sustain the fishing activities and develop the economic condition of the fisherman are analyzed. This study revealed that the economic status of fishing boat owners fluctuated around the poverty line, secondary and low-level workers such as skippers, crew members, and others were heavily affected.